WNK3 Maintains the GABAergic Inhibitory Tone, Synaptic Excitation and Neuronal Excitability via Regulation of KCC2 Cotransporter in Mature Neurons - Lim, Wee Meng (Frontiers Media S.A., 2022)
10.3389/fnmol.2021.762142